The law of the of the iterated logarithm for Non-stationary Markov chains - Kuchkarov, J. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Я. Х. Кучкаров, Закон повторного логарифма для неоднородных цепей МарковаJ. Kučkarovas, Kartotinio logaritmo dėsnis nehomogeninėms Markovo grandinėms